1971
DOI: 10.1073/pnas.68.7.1542
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Colonies of Hemoglobin-Synthesizing Cells by Erythropoietin In Vitro

Abstract: A culture method has been developed in which erythroid colonies are produced in vitro from hemopoietic cells from the livers of 13-day fetuses of C3Hf/Bi mice. Heme synthesis by the cultures was correlated with the presence of these colonies, and the hemoglobin produced was shown to be electrophoretically normal. The individual colonies were identified as erythroid since they were erythropoietin-dependent, positively stained by the histochemical 'Lepehne' procedure for hemoglobin, and labeled by 59Fe radioauto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
182
0
2

Year Published

1972
1972
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(186 citation statements)
references
References 17 publications
2
182
0
2
Order By: Relevance
“…It was also shown that the hematopoietic cell colonies in culture can originate from single cells (Ginsburg and Sachs, 1963;Pluznik and Sachs, 1966;Paran and Sachs, 1969) and are therefore clones which develop from precursor cells that survived, multiplied and di erentiated to mature cells in culture. The procedure for clonal growth of mouse macrophages and granulocytes in agar (Pluznik and Sachs, 1965) was then also used by others (Bradley and Metcalf, 1966), and was applied to the clonal development of normal human macrophages and granulocytes (Paran et al, 1970;Pike and Robinson, 1970) and other blood cell lineages (Stephenson et al, 1971;Metcalf et al, 1975;Gerassi and Sachs, 1976).…”
Section: Clonal Development Of Normal Hematopoietic Cells In Culturementioning
confidence: 99%
“…It was also shown that the hematopoietic cell colonies in culture can originate from single cells (Ginsburg and Sachs, 1963;Pluznik and Sachs, 1966;Paran and Sachs, 1969) and are therefore clones which develop from precursor cells that survived, multiplied and di erentiated to mature cells in culture. The procedure for clonal growth of mouse macrophages and granulocytes in agar (Pluznik and Sachs, 1965) was then also used by others (Bradley and Metcalf, 1966), and was applied to the clonal development of normal human macrophages and granulocytes (Paran et al, 1970;Pike and Robinson, 1970) and other blood cell lineages (Stephenson et al, 1971;Metcalf et al, 1975;Gerassi and Sachs, 1976).…”
Section: Clonal Development Of Normal Hematopoietic Cells In Culturementioning
confidence: 99%
“…In the experiments with bone marrow 10' cells were plated. The progenitor cell yielding the red cell colonies is referred to as "CFU-E" (colony-forming unit, erythroid) ' (10,11). RESULTS Some erythroid colonies developed from fetal mouse liver cells plated in methyl cellulose containing no added erythropoietin.…”
Section: Introductionmentioning
confidence: 99%
“…1). Dexamethasone inhibited colony formation at concentra- Iof-10 9 10-10 1o-11 10 Cultures contain 0.5 U sheep erythropoietin.…”
Section: Introductionmentioning
confidence: 99%
“…Erythroid colony formation by precursors in the fetal liver or marrow has been described in plasma gel and methylcellulose cultures (1)(2)(3)(4). In agreement with earlier work in vio, the proliferation of erythropoietic cells in vitro appears to be dependent on a factor tentatively characterized as erythropoietin (5).…”
mentioning
confidence: 99%